Pengaruh Good Corporate Governance, NonPerforming Financing, Dan Financing to Deposit Ratio Pada Kinerja Keuangan - Nyoman Sri Wahyuni (UNHI Press, 2023)
ABSTRACT Return on Assets (ROA) is part of the profitability ratios in analyzing financial reports on company financial performance reports. The purpose of this research is to examine the influence of Good Corporate Governance (GCG), Non Performing Financing (NPF), and Financing to Deposit Ratio (FDR). Against Financial Performance. The population in this study are 14 Islamic banks listed on the Indonesia Stock Exchange from 2018-2021. The samples in this study were 14 Islamic banking companies with a 4 year period so that the total sample used was 56 samples. The analysis technique used in this study is multiple linear aggression. The results of the analysis show that Good Corporate Governance (GCG) has a positive effect on financial performance in Islamic banks with a t count of 2,807 and a significance of 0,007 <0.05, Non Performing Financing (NPF) has a negative effect on Islamic financial performance, with a t count of -3,767 equal to and significance of 0.000 <0.05, and 3. Financing To Deposit Ratio (FDR) has a positive effect on the financial performance of Islamic banking companies, with a t-value of 6,276 and a significance of 0.000 <0.05. ABSTRAK Return on Asset (ROA) merupakan bagian dari rasio profitabilitas dalam menganalisa laporan keuangan atas laporan kinerja keuangan perusahaan. Tujuan dari penelitian ini adalah unutk menguji pengaruh Good Corporate Governance (GCG), Non Performing Financing (NPF), dan Financing to Deposit Ratio (FDR). Terhadap Kinerja Keuangan. Populasi dalam penelitian ini ialah 14 perbankan syariah yang terdaftar Bursa Efek Indonesia terhitung dari tahun 2018-2021. Adapun sampel dalam penelitian ini ialah yakni 14 perusahaan perbankan syariah dengan periode 4 tahun sehingga total sampel yang digunakan yakni 56 sampel. Teknik Analisis yang digunakan dalam penelitian ini, adalah agresi linear berganda. Hasil analisis menunjukkan bahwa Good Corporate Governance (GCG) berpengaruh positif terhadap kinerja keuangan pada bank syariah dengan t hitung sebesar 2.807 dan signifikansi 0.007 < 0,05, Non Performing Financing (NPF) berpengaruh negatif terhadap kinerja keuangan syariah, dengan nilai t hitung -3.767 sebesar dan signifikansi 0,000 < 0,05, dan 3. Financing To Deposit Ratio (FDR) berpengaruh positif terhadap kinerja keuangan perusahaan perbankan syariah, dengan nilai t hitung sebesar 6.276 dan signifikansi sebesar 0,000 < 0,05.